Alzheimer’s Care: Getting Better - Pate, Jenna (My University, 2015)
As I was growing up, I still remember going to my grandparents’ house every day after elementary school and eating orange sherbet, riding bikes around the neighborhood, and going to the library to get books to read. I saw my grandparents so much as a child that they basically helped to raise me alongside my parents. They were the only grandparents I knew, since my father’s parents had passed long before I was brought into this world. I was their only granddaughter out of four grandchildren as well, so there was a special bond there that cannot even begin to be compared with anything else. Both of my grandparents were eventually diagnosed with Alzheimer’s disease. It affected both of their lives dramatically, as well everybody in my family’s lives. The treatments and therapies for Alzheimer’s disease are rapidly evolving, which is great news for future generations.
2015 W. Keats Sparrow Writing Award, Second Place Winner
Keywords: Alzheimer's disease; Neurodegenerative disease; Behavioral therapy; Drug therapy